IWMI Annual Report 2024: INSIGHTS IN MOTION - International Water Management Institute (International Water Management Institute, 2025)
For the International Water Management Institute’s (IWMI), 2024 was defined by strong scientific research, strategic partnerships, and advances in water security across the Global South. 2024 was a key year for the organization, reflecting on its legacy as it celebrated its 40th anniversary and looking ahead as it launched its new IWMI Strategy 2024–2030.